The administrative criminal penalty in Iraqi and comparative law - mousa, Adnan; Al-Shimari, Dr. Kadhim (Journal of Legal Sciences, 2021)
The administrative criminal penalty is one of the most important forms of punishment reduction, rationalization of criminalization and reduction of criminal proceedings, this type of punishment is related to minor crimes, in which the act is an administrative offense stipulated by the law and the administration is punished by administrative procedures, With the need for judicial guarantee to ensure the right to appeal administrative sanctions before the judiciary, and criminal legislation that took this type of penalty act to remove contraventions from the Penal Code to include only crimes and misdemeanors. The Iraqi Penal Code continues to be based on the tripartite division of crimes (crimes, misdemeanors, contraventions). However, the legislator has facilitated criminal proceedings by authorizing criminal authorities to administration but has failed to regulate the legal procedures on which administrative sanctions are imposed. And administrative sanctions in Iraqi law are not subject to uniform legal rules to reflect their nature in terms of the nature of such sanctions and the appropriate procedures for their imposition.